Persepsi Petani terhadap Program IPDMIP (Integrated Participatory Development and Management Irrigation Program) - Winnita Sherlynda; Eny Lestari; Putri Permatasari (Jurnal Sosial Ekonomi Pertanian, 2022)
In Margorejo Subdistrict, Pati Regency, researchers sought the opinion of farmers on the IPDMIP program. (1) to find out how the farmers view the IPDMIP program, and (2) to see the relationship between the perception-forming elements and the farmers' perspective on the IPDMIP. In this study, the main data collection technique was through an interview procedure which included the use of a questionnaire. Spearman rank correlation was used to test the data. Based on the findings: 1) Farmers' perceptions of the IPDMIP program are positive, as evidenced by their perceptions of the benefits of the program, IPDMIP field school activities, and technological innovation; 2) perception-forming factors that have a significant relationship are age and formal education; 3) Perception-forming factors that do not have a significant relationship are land area, income, environment, social status, and the role of agricultural extension workers.